Entrepreneurial Education For Finger Disabilities Deaf Talk Training Through Processing Bread - Novfitri Landong Namora Sihombing Novfitri Sihombing; Siti Rozinah; Andri Meiriki (Yayasan Ilomata, 2020)
Competition increasingly harsh world of work and a lot of people who have not equalized the ability of the deaf to make them more challenging to grow and live independently. Still, there who think that people with smallpox are the ones who made the other person. Though there are still people with disabilities who have the talent and it can lift more appreciated in rank than the healthy surrounding environment. Could take the lesson that not all people with disabilities harm others. Normal Supposedly embarrassed and could make the experience from these people if see the concept, entrepreneurship be entrepreneurial while their entrepreneurship taste of the French language